Validation of the Russian Version of the MoCA Test as a Cognitive Screening Instrument in Cognitively Asymptomatic Older Individuals and Those With Mild Cognitive Impairment - Freud, Tamar; Vostrikov, Anna; Dwolatzky, Tzvi; Punchik, Boris; Press, Yan (Frontiers in Medicine, 2020)
Background: Mild Cognitive Impairment (MCI) in older people is a common syndrome that should be recognized, since interventions such as physical exercise and cognitive training may be useful in maintaining cognitive function and planning for the future is useful. The MoCA test is a useful screening instrument for MCI, but the Russian version of this test has not yet been validated in this condition. The aim of the present study was to validate the Russian version of the MoCA test. Methods: The study population included 160 residents of Israel aged 65 years and older with Russian as their mother tongue, 80 with a clinical diagnosis of MCI, and 80 cognitively asymptomatic controls (AC). All participants underwent cognitive evaluation the Russian version of the MoCA test (MoCA-Ru), and a computerized cognitive assessment battery (Neurotrax) validated for MCI. Results: The mean age of the study population was 78±6.6 years and 123 (76.9%) were women. The MoCA-Ru score was higher in the AC group than in those with MCI (24.3±3.74 vs. 20.2±3.07, P<0.0001). Based on ROC analysis MoCA-Ru was found to have good discriminating capacity for differentiating participants with MCI from asymptomatic controls at a cutoff value of 25. Conclusions: We found the Russian language version of the MoCA test to be useful as a screening tool for MCI. However, there is a need for further adaptation and validation of the current Russian version of the MoCA.